REVERSE LOGISTICS IN THE RUSSIAN ORGANIZATIONS: THEORETICAL AND PRACTICAL ASPECTS - A. Kanke; O. Aleksandrov (Вестник университета)
The arguments proving necessity of development of the logistic management concept by material, information, financial and returnable flows are provided. The problems of the Russian logistics connected with its efficiency, the quality level and questions of processing (utilization), correction of defective products (works, services) - returnable (reverse logistics), or logistics of returnable flows are considered. The most typical stages of management of reverse flows are allocated. Problems of reverse logistics of organizational and methodical character are systematized. Actions for the solution of the designated problems are offered.